Delineation of Groundwater Potential Zones Using Geoinformatics and AHP Techniques in Central Erbil Sub-basin, Kurdistan Region, Iraq - Mzuri, Rebar T.; Jirjees, Shevan Jameel; Hamed, Masoud Hussein (Iraqi Journal of Science, 2026)
The most dependable source of fresh water is groundwater. Several factors, including urbanization, industry, and population growth, seriously endanger groundwater supplies. The amount and quality of groundwater supplies are significantly impacted by climate change. The Erbil sub-basin is the area of the study, where groundwater rather than surface water is the primary supply for agricultural and residential purposes. To determine the possible groundwater zones, many parameters such as rainfall, elevation, slope, drainage density, land use and cover, and lineament density are created as separate layers using GIS techniques and then put through a weighted overlay analysis. The analytical hierarchy process (AHP) was utilized to assign the weights for the different layers. In addition, the three categories of high, moderate, and low zones were stated in the GWPZ final map. Based on the data, the "High GWPZ" covers approximately 575.44 km2 (21.24%), the "Moderate GWPZ" covers 1836.40 km2 (67.80%), and the "Poor GWPZ" covers 296.81 km2 (10.96%). Furthermore, the study's findings showed that the rainfall factor had the zone with the most substantial and adequate groundwater potential. The effect of rainfall served as the primary groundwater storage source. Thus, groundwater recharge rises conversely with increasing rainfall intensity. In addition, a strong connection was seen between the results and the well-static water level data used to validate the results. As dependable findings were produced with the proposed technique, future management plans incorporating natural and artificial recharge practices may be created in these locations with effectiveness.